DESCOURSE BETWEEN TEACHER AND STUDENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The discourse between teacher and student plays a pivotal role in shaping educational experiences and outcomes. This interaction extends beyond the simple exchange of information, encompassing a dynamic process of negotiation, understanding, and mutual growth. Effective teacher-student discourse fosters critical thinking, promotes engagement, and supports the development of both cognitive and emotional intelligence. Through various forms dialogue, questioning, feedback, and discussion this communication forms the backbone of a responsive and inclusive learning environment. This theme explores how discourse patterns reflect pedagogical strategies, cultural contexts, and individual learner needs, ultimately highlighting the importance of communicative competence in education.